Metabolomics-Driven Exploration of the Antibacterial Activity and Mechanism of 2-Methoxycinnamaldehyde - Qian, Chunguo; Jin, Lu; Zhu, Longping; Zhou, Yang; Chen, Jing; Yang, Depo; Xu, Xinjun; Ding, Ping; Li, Runnan; Zhao, Zhimin (Frontiers in Microbiology, 2022)
Methicillin-resistant Staphylococcus epidermidis (MRSE) is one of the most commonly seen pathogens which may cause uncontrollable infections in immunocompromised and hospitalized patients. The compounds isolated from Cinnamon, such as cinnamaldehyde, cinnamic acid showed promising anti-oxidative, anti-tumor, and immunoregulatory effects, more important, these compounds also possess promising broad-spectrum antibacterial activity. In this study, the potential antibacterial activity of 2-methoxycinnamaldehyde (MCA), another compound in cinnamon, against MRSE was investigated. Combining broth microdilution test, live/dead assay, and biofilm formation assay, we found MCA was able to inhibit the proliferation, as well as the biofilm formation of MRSE, indicating MCA could not only affect the growth of MRSE but also inhibit the pathogenic potential of this bacterium. Additionally, the results of scanning electron microscopy (SEM) and transmission electron microscopy (TEM) demonstrated that MCA caused morphological changes, the leakage of DNA, RNA, and cellular contents of MRSE. Due to the close relationship between cell wall synthesis, ROS formation, and cell metabolism, the ROS level and metabolic profile of MRSE were explored. Our study showed MCA significantly increased the ROS production in MRSE, and the following metabolomics analysis showed that the increased ROS production may partially be due to the increased metabolic flux through the TCA cycle. Besides, we noticed the metabolic flux through the pentose phosphate pathway (PPP) was upregulated accompanied by elevated ROS production. Therefore, the alterations in cell metabolism and increased ROS production could lead to the damage of the cell wall, which in turn decreased the proliferation of MRSE. In conclusion, MCA seemed to be a promising alternative antimicrobial agent to control MRSE infections.